On the efficiency of the Malaysian banking Sector: a risk-return perspective - Sufian, Fadzlan; Haron, Razali (Emerald Group Publishing Limited, 2009)
The purpose of this paper is to examine the efficiency of the Malaysian banking sector.The technique used by Oliveira and Tabak is extended by employing market data as input and output variables to individual bank stocks, which are listed on the Kuala Lumpur Stock Exchange (KLSE). By doing this, the paper aims to broaden the scope of the existing studies by employing individual bank market data to measure their efficiency levels. The paper utilizes the non-parametric data envelopment analysis methodology to measure the efficiency of banks which are listed on the KLSE. While previous bank efficiency studies have used balance sheet and income statements data, this paper uses individual bank’s market data as the input and output variables to construct the efficiency frontier. The main conclusion of this paper is that the most efficient bank is also highly ranked in terms of returns with relatively low standard deviation and beta. The results also suggest that all the banks which have managed to appear on the efficiency frontier are mainly based on the relatively higher mean returns rather than lower standard deviations and/or beta. Research limitations/implications – The approach used in this paper could also be used to other economic sectors, as well as from a multiple countries perspective as this approach allows the comparison of different countries, which have different accounting rules and are not comparable by using standard models. The approach could also be extended to incorporate other input(s) and/or output(s) which could further add to the robustness of the results. The contribution of the paper consists of proposing a new approach to the measurement of bank efficiency.